Why Do B–P and Al–P Polymers Differ? Structures, Stability, and Electronic Properties of Chain and Ring [H2PEH2]n Oligomers (E=B, Al; n=1–15). Issue 64 (24th October 2018) - Pomogaeva, Anna V.; Scheer, Manfred; Timoshkin, Alexey Y.
Abstract: Chain and ring [H2 PEH2 ] n oligomers (E=B, Al; n =2–15) have been computationally studied at the B3LYP/def2‐TZVP level of theory. A strong tendency to cyclization was found for the chain Al–P oligomers with n >7, whereas analogous long B–P oligomers can exist as chain structures. Subsequent oligomerization enthalpies approach each other very closely for the ring and chain oligomers with an increase of n . However, these oligomers have very different electronic properties with band gaps below 0.2 eV for the chain [H2 PBH2 ]15 and more than 5 eV for the ring isomer [H2 PEH2 ]15 . The molecular orbitals in the ring oligomers are highly delocalized, whereas for the chain isomers, the HOMO and LUMO are localized at the different ends of the oligomeric chain. Abstract : Aim for the stars ! The computational study of chain and ring [H2 PEH2 ] n oligomers demonstrates the substantial differences between the oligomerization of phosphinoboranes and phosphinoalanes. Al–P chains have a pronounced donor–acceptor character and exhibit a much stronger tendency to cyclization. Although B–P rings are analogous to cyclic oligoethylene structures, Al–P rings adopt different (star‐like) conformations (see figure).